2021
DOI: 10.3390/ijerph18158133
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle in Undergraduate Students and Demographically Matched Controls during the COVID-19 Pandemic in Spain

Abstract: Few studies have used a multidimensional approach to describe lifestyle changes among undergraduate students during the COVID-19 pandemic or have included controls. This study aimed to evaluate lifestyle behaviors and mental health of undergraduate students and compare them with an age and sex-matched control group. A cross-sectional web survey using snowball sampling was conducted several months after the beginning of COVID-19 pandemic in Spain. A sample of 221 students was recruited. The main outcome was the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 52 publications
(71 reference statements)
1
8
0
1
Order By: Relevance
“…These results converge with those of previous studies that analyzed mental health among university students and, more precisely, health sciences students [ 39 , 40 ]. Previous surveys suggest the potential risk for a less healthy lifestyle in those undergraduate students with a history of mental illness in the previous year or a positive screening for depression and anxiety [ 18 , 41 ]. Therefore, there may be a relationship between the perceived low quality of life (e.g., vitality) and poor mental health reported by female students in our sample.…”
Section: Discussionmentioning
confidence: 99%
“…These results converge with those of previous studies that analyzed mental health among university students and, more precisely, health sciences students [ 39 , 40 ]. Previous surveys suggest the potential risk for a less healthy lifestyle in those undergraduate students with a history of mental illness in the previous year or a positive screening for depression and anxiety [ 18 , 41 ]. Therefore, there may be a relationship between the perceived low quality of life (e.g., vitality) and poor mental health reported by female students in our sample.…”
Section: Discussionmentioning
confidence: 99%
“…The SMILE-C shows an overall Cronbach’s alpha value of 0.75 and Kaiser–Meyer–Olkin measure of 0.77 [ 16 ]. This scale was simultaneously developed in three languages: English, Spanish, and Portuguese [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Findings from our study are in line with reports previously discussed, highlighting the relationship between different lifestyle domains, such as diet, physical activity, social relationships, and sleep quality, and symptoms of common mental health problems, 11 , 26 - 28 which have been further emphasized during the COVID-19 pandemic around the world. 15 , 16 …”
Section: Discussionmentioning
confidence: 99%
“… 7 , 13 , 14 The relationship between these factors with mental health symptoms and disorders has been further emphasized during the COVID-19 pandemic, with the home-confinement measures introduced around the world leading to lifestyle changes in North Africa, Western Asia, and Europe. 15 , 16 The urgency to suddenly change many aspects of these lifestyle behaviors has led to serious negative impacts on people’s overall mental well-being. In Brazil, a study found a positive association between the presence of psychological symptoms (e.g., depression, anxiety, and stress) and social isolation variables (e.g., days of isolation, loneliness, and social distancing) adopted for containment of the wide-spreading virus.…”
Section: Introductionmentioning
confidence: 99%